Methodological bias in social work education: the silence of quantitative approaches in students' research in Zimbabwe. - Muzingili, Taruvinga; Magocha, John Chiwanza; Taruvinga, Raymond (Social Work Education, 2025)
This study examines the factors contributing to the low utilization of quantitative research approaches among social work research students. A census sampling technique was employed to conduct a survey of 1268 students who had completed their final year research dissertations. The descriptive statistics revealed that 81% (n = 1022) of social work students employed qualitative research, 16% (n = 208) used mixed methods, and only 3% (n = 38) utilized quantitative approaches. A multiple linear regression analysis revealed factors that were statistically significant (ρ<.05) in predicting low utilization of quantitative approaches that include; the supervisor's preference, the student's secondary education, training in research methods, competency in statistics, methodological flexibility and suitability, resources constraints, professional assistance, and fear of failure. These findings prompt recommendations for social work training institutions to enhance their research capacity, adopt co-supervisions, advocate for quantitative research, and prioritize continuous research mentorship in statistical tools.